Action of MK‐7264 (gefapixant) at human P2X3 and P2X2/3 receptors and in vivo efficacy in models of sensitisation. (11th May 2019) - Richards, David; Gever, Joel R.; Ford, Anthony P.; Fountain, Samuel J.
Abstract : Background and Purpose: The P2X3 receptor is an ATP‐gated ion channel expressed by sensory afferent neurons and is used as a target to treat chronic sensitisation conditions. The first‐in‐class, selective P2X3 and P2X2/3 receptor antagonist, the diaminopyrimidine MK‐7264 (gefapixant), has progressed to Phase III trials for refractory or unexplained chronic cough. We used patch clamp to elucidate the pharmacology and kinetics of MK‐7264 and rat models of hypersensitivity and hyperalgesia to test its efficacy on these conditions. Experimental Approach: Whole‐cell patch clamp of 1321N1 cells expressing human P2X3 and P2X2/3 receptors was used to determine mode of MK‐7264 action, potency, and kinetics. The analgesic efficacy was assessed using paw withdrawal threshold and limb weight distribution in rat models of inflammatory, osteoarthritic, and neuropathic sensitisation. Key Results: MK‐7264 is a reversible allosteric antagonist at human P2X3 and P2X2/3 receptors. Experiments with the slowly desensitising P2X2/3 heteromer revealed concentration‐ and state‐dependency to wash‐on, with faster rates and greater inhibition when applied before agonist compared to during agonist application. The wash‐on rate ( τ value) for MK‐7264 at maximal concentrations was much lower when applied before compared to during agonist application. In vivo, MK‐7264 displayed efficacy comparable to naproxen in inflammatory and osteoarthritic sensitisation models and gabapentin in neuropathic sensitisation models, increasing paw withdrawal threshold and decreasing weight‐bearing discomfort. Conclusions and Implications: MK‐7264 is a reversible and selective P2X3 and P2X2/3 antagonist, exerting allosteric antagonism via preferential activity at closed channels. Its efficacy in rat models supports its clinical investigation for chronic sensitisation conditions.